Sun safety knowledge and practice in UK postal delivery workers - Houdmont, Jonathan; Davis, S.; Griffiths, A. (Oxford Journals, 2016)
Background: Postal delivery workers spend a large proportion of their work time outdoors, placing them at increased risk for skin cancer. To date, no studies have examined occupational sun safety knowledge and practice within this group in the UK. Aims: To describe the occupational sun safety knowledge and practice of UK postal delivery workers and to investigate the association of demographic, personal and occupational factors with knowledge and practice in order to identify potential strategies for improving sun safety in this occupational group. Methods: Postal delivery workers completed a questionnaire that collected data on occupational sun safety knowledge and practice in addition to demographic, personal and workplace characteristics. One-way analysis of variances were applied to assess differences in knowledge and practice by these characteristics. Results: A total of 1153 postal delivery workers completed the questionnaire, a 60% response rate. Thirty three per cent reported receiving sun safety training within the previous 12 months. The majority of respondents reported correct knowledge on three of the six domains and good practice on four of the six behavioural domains. However, only one-fifth of respondents reported wearing sunglasses and ensuring a plentiful intake of water. Knowledge and practice differed significantly according to demographic, personal and workplace characteristics. Conclusions: There is a need to raise the profile of occupational skin cancer in this occupational group and to increase the priority given to occupational sun safety policies alongside targeted and tailored interventions, the effect of which can be evaluated.